(untitled) (Bangladesh Journal of Animal Science, 2012)
This study was conducted to compare the productive and reproductive performance of indigenous and crossbred cow likely Friesian, Sahiwal and Sindhi cross. A total of 180 dairy cows were selected randomly from four upazilas of Comilla district. It was observed that mean milk yield and lactation length of indigenous, Friesian cross, Sahiwal cross and Sindhi cross were 2.35±0.04, 7.36±0.11, 4.78±0.08 and 4.03±0.05 litre/day and 218.22±8.35, 284.69±1.64, 251.77±3.66 and 259.77±4.91 days respectively. It reveals that the Friesian cross is the best performer in relation to milk production and lactation length. About the reproductive performances it shows that indigenous cows need minimum (1.81±0.048) services per conception. Gestation length was shorter in case of Sahiwal cross (277.64±1.99 days) and it varies within Friesian and Sindhi cross in a short range (278.77±1.38 to 279.31±1.00 days). Calving interval was lower in Friesian crosses (413.77±53.87 days) than its counterparts. Age at puberty was shorter in Friesian cross (662.44±2.52 days). It interprets that Friesian cross was the best performer than other crossbred and indigenous cows in dairy potentialities. DOI: http://dx.doi.org/10.3329/bjas.v37i1.9866 BJAS 2008; 37(1): 39-43